The effectiveness of trusts, including companies within a trust structure, as a tax saving mechanism in relation to investment property - Naidoo, Shanolan (My University, 2021)
This report analyses the tax benefits and disadvantages of utilising a trust as an investment vehicle for residential property investment versus purchasing these in one's individual capacity. It also assesses if the trust can be utilised as part of a wider structure involving companies to legitimately reduce the effective tax liability of the investor while still being able to extract value from the investment. The tax consequences of the various investment vehicles (natural person, trust, company) have been assessed in relation to an investment property portfolio. This assessment includes current tax, capital gains tax, estate duty, anti-avoidance (such as section &C), specific property related legislation (such as sections 13sex), as well as specific scenarios involved in property investment (such as the fact that these will typically generate losses during the initial years of investment). Based on analysis of the various types of taxes that has been performed, it is clear that there is no standard solution indicating that one investment vehicle is more suitable than the other. The most tax efficient vehicle is dependent on how much the individual earns in a tax year, whether the investment property portfolio is loss or profit making, the intention and business model involved (whether to hold for long term appreciation or to sell), the type of investment property being purchased (such as whether these would qualify for special allowances such as 13sex), the value of the portfolio involved, whether these would generate capital gains or losses upon sales, etc.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Commerce (in Taxation), 2021
Keywords: UCTD; Trusts; Residential property; Tax avoidance; South Africa; Tax liability; Rental income; Capital gain; Property investment; SDG-8: Decent work and economic growth